The Treatment of Lunar Eclipses in Babylonian Omen Astrology: Епūmа Anu Enlil Tablets 15-22 - Rochberg-Halton, Francesca (1980)
Ph.D. Dissertation; cf. JCS 36 (1984) 138, fn. 49; wird demnächst als AfO Beiheft 22 erscheinen; vorläufiger Titel: Aspects of Babylonian Celestial Divination: The Lunar Eclipse Tablets of Епūmа Anu Enlil.